THE EFFECT OF TIME BUDGET PRESSURE, AUDIT OPINION, AND AUDIT QUALITY ON AUDITOR SWITCHING IN MANUFACTURING COMPANIES IN THE FOOD AND BEVERAGE SUBSECTOR LISTED ON THE INDONESIA STOCK EXCHANGE - Sutra Meilani Rizki; Leriza Desitama Anggraini; RM Rum Hendarmin (JEA17: Jurnal Ekonomi Akuntansi, 2026)
Auditor switching can occur either voluntarily or mandatorily. This study aims to analyze the effect of time budget pressure, audit opinion, and audit quality on auditor switching in food and beverage manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the 2019-2023 period. The research sample consists of 15 companies selected using purposive sampling, resulting in a total of 75 observations over five years. This study employs a quantitative approach using logistic regression analysis to examine the relationship between independent and dependent variables. The results show that time budget pressure significantly affects auditor switching, with a significance value of 0.022 (<0.05). Audit opinion also has a significant impact on auditor switching, with a significance value of 0.045 (<0.05). In contrast, audit quality does not significantly influence auditor switching, with a significance value of 0.466 (>0.05). These findings indicate that companies are more likely to switch auditors when facing time pressure during the audit process or receiving an audit opinion that does not meet management’s expectations. Meanwhile, audit quality is not the primary factor in auditor switching decisions, as companies prioritize cost and time efficiency. This study provides implications for auditors and regulators in understanding the factors influencing auditor switching and highlights the importance of managing time budget pressure to maintain audit quality.